The economics of the volunteering decision - Sardinha, Boguslawa Mária Barszczak (2015)
One objective of this work is to explore and test several explanatory models of volunteering activity. This thesis identi es the factors that determine whether individuals volunteer or not, considering both volunteering in general as well as volunteering in particular types of activities. The factors analyzed include demographic and socioeconomic variables, attitudinal variables and the country of origin. We identify four types of volunteering: social awareness volunteering, political and professional volunteering, educational and leisure volunteering and social justice volunteering. The thesis also studies the interdependencies between the various types of volun- teering and analyzes the volunteering decision as a choice among mutually exclusive alternatives that include the possibility of doing simultaneously more than one type of volunteering activity. Another objective of this work is to explore the motivations for volunteering, to identify the relationship between these motivations and the various types of volunteering work, and to perform an exploratory analysis of the determinants of the di¤erent types of motivations. We identify and test three main motivations for volunteering: altruistic motivations, warm glow social oriented motivation and warm glow ego driven motivation. The empirical part of this dissertation was based on the second and fourth waves of the World Value Survey and the European Value Survey; RESUMO: Um dos objectivos do presente trabalho é identificar e testar vários modelos explicativos do voluntariado. Procuramos, por conseguinte, identificar os factores determinantes na decisão de abraçar as actividades voluntárias, tanto no geral como em actividades/sectores específicos. Para o efeito reunimos os vários factores identificados nos seguintes grupos: demográficos, sócio-económicos, atitudinais e por país. São identificados quatro tipos específicos de voluntariado: voluntariado de consciência social, voluntariado político e profissional, voluntariado educacional e de lazer e voluntariado de justiça social. Um outro objectivo desta tese é explorar as diferentes motivações para o voluntariado e identificar as suas relações com os diversos tipos de voluntariado praticado. Foram considerados três tipos de motivações: altruísta, warm glow de orientação social e warm glow de orientação egoísta. Para além disso, introduzimos no trabalho uma abordagem exploratória dos factores que influenciam as motivações. O suporte empírico para as análises e testes efectuados foi a base de dados de onda dois e onda quatro da World Value Survey e da European Value Survey.